Outcomes of incoming and outgoing second opinions from a UK liver transplant centre. Issue 1 (14th September 2022) - Parente, Alessandro; Boyd, Alexander; Mahgoub, Sara; Morris, Sean; Webb, Kerry; Neuberger, James; Armstrong, Matthew J; Rajoriya, Neil
Abstract : Objective: Second transplant centre opinions (STCOs) for patients declined for liver transplantation are infrequent. We aimed to identify STCOs outcomes from a tertiary transplant centre. Design: Referrals between 2012 and 2020 to Birmingham Unit were reviewed. Incoming: all referrals from out-of-region centres were collated. Outgoing: patients not listed in Birmingham were reviewed to identify referrals for STCOs to the other UK centres (A–F). Results: 2535 patients were assessed for liver transplantation during the study period. Incoming: among 1751 referrals, 23 STCOs (17 unit A, 3 unit B, 1 unit C, 1 unit D and 1 unit E) were provided by Birmingham. Of the STCOs, 13/23 (57%) patients remained unsuitable for transplantation. Therefore, 10/23 (43%) underwent a second liver transplant assessment, of whom five (50%) were still deemed unsuitable, three (30%) listed (one transplanted) and two (20%) died preassessment. Outgoing: among 426 patients not listed, eight (1.8%) patients were referred for STCO (4 unit E, 2 unit B, 1 unit D, 1 unit A). Three (38%) were listed, two (25%) were assessed and declined, two (25%) were unsuitable for assessment and one (12.5%) died while waiting. Combining incoming and outgoing Birmingham STCOs (n=31), six (19%) of STCOs were listed in a second centre. Conclusion: Second transplant centre opinions are rare with the majority still deemed unsuitable for liver transplantation. This highlights potential resource implications especially when undergoing a full second formal assessment. A streamlined STCO process with sharing of investigations and use of telemedicine in appropriate patients may allow for greater transparency, quicker decision making and less use of labour-intensive resources.